Karakterisasi Struktur Anatomi Kayu Pada Beberapa Genus Dalam Famili Sapindaceae Di Sumatera Barat - Mega Eka Putri; Tesri Maideliza; Nurainas Nurainas (Universitas Andalas, 2015)
Anatomical structure characterization of some wood genus of Sapindaceae in West Sumatra was conducted from May to October 2015 with survey and direct observation method. Cluster analysis conducted using PAST program to determine relationship among genus investigate on present study. The woods of nine genus namely Filicium, Nephelium, Pometia, Guioa, Xerospermum, Sapindus, Harpullia, Lepisanthes and Mischocarpus were analyzed. All of i.e, character vessels, parenchyma, rays and fibre morphology were analyzed by using permanent slide based on Sass (1958) procedured. The results showed all of woods have same type of porous namely diffuse porous. Type of vessel distribution namely soliter in Xerospermum and multiple in Filicium, Nephelium, Pometia, Guioa, Sapindus, Harpullia, Lepisanthes and Mischocarpus. Xylem parenchym type namely apotracheal in Pometia and Lepisanthes and paratracheal in Filicium, Nephelium, Guioa, Xerospermum, Sapindus, Harpullia and Mischocarpus. Rays type namely uniseriate type in Nephelium, Pometia, Sapindus, Harpullia and Lepisanthes and multiseriate type in Filicium, Guioa, Xerospermum and Mischocarpus. Rays composition namely heterocellular in Filicium, Sapindus, Harpullia and Nephelium and homocellular in Mischocarpus, Lepisanthes, Pometia, Xerospermum and Guioa. Fiber size is long chategory in Nephelium genus, medium in Filicium, Xerospermum, Harpullia and Lepisanthes, and short chategory in Pometia, Sapindus, Guioa, and Mischocarpus. Cluster analysis showed up among genus present of two cluster namely uniseriate rays cluster and multiseriate rays cluster. Both the cluster genus member showed clustering tightly except Nephelium genus weakly clustering in the multiseriate cluster do to have different fiber size chategory from the other genus. The character of woods using at present study useful as additional character of morphologically data to determine of genus taxa.Keywords : anatomical structure, family Sapindaceae, permanent slide, relationship